Analysis of the Effect of Brand Equity, Brand Perception and Brand Loyalty on the Purchase Decision of Nevada Brand Clothes (Study Case: Matahari Department Store Medan) - Slamet Widodo; Lambok Manurung (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study was to test and analyze whether brand equity, brand perception and brand loyalty influence the purchasing decisions of Nevada brand clothing. The type of research used in this research is associative (casual) research. The population in this study were 70 consumers who shop for Nevada brand clothing at Matahari Department Store Medan. The sampling technique used purposive sampling method with a total sample of 60 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the research hypothesis is multiple regression test. The results showed that the influence of brand equity, brand perception and brand loyalty had a positive and significant effect on purchasing decisions with Fcount of 12.32 while Ftable was 2.27 and significant 0.025 <0.05. The results of the regression analysis also obtained a coefficient of determination (R2) of 0.719 which can be called the coefficient of determination which in this case means that 71.9% of purchasing decisions can be obtained and explained by brand equity, brand perception and brand loyalty. While the remaining 100% - 71.9% = 28.1% is explained by other factors outside of variables such as brand awareness, price and others